Reduction of CAII Expression in Gastric Cancer: Correlation with Invasion and Metastasis - Li, Xiao-jie; Xie, Hai-long; Lei, San-ju; Cao, Hui-qiu; Meng, Tian-Yun; Hu, Yu-lin (Chinese Journal of Cancer Research; Vol 24, No 3 (September 01, 2012): Chinese Journal of Cancer Research, 2012)
Objective: Human carbonic anhydrases II (CAII) gene plays an important role in different cancer. However, its relevance to gastric cancer (GC) remains unclear. In the present study, we aimed to investigate the expression of CAII in GC and explore its correlation with some clinicopathologic characteristics of GC. Methods: The expression of CAII in 20 specimens of normal gastric mucosa, 38 specimens of intraepithelial neoplasia and 112 specimens of gastric carcinoma were detected by immunohistochemical techniques. Survival in GC with CAII expression was studied. Results: The positive rate of CAII protein in normal gastric mucosa was significantly higher than that in intraepithelial neoplasia and gastric carcinoma (100% vs. 63.16% and 28.57%, P